Rediscovering corruption’s other side: bribing for peace in post-conflict Kosovo and Chechnya - Zabyelina, Yuliya (Crime, law and social change, 2013)
Conventional approaches towards the impact of corruption on post-conflict stabilization suggest that corrupt practices impede a successful war to peace transition. When transparency and accountability are absent, the risk of corruption threatens to turn the state apparatus into a tool of enrichment for those in power and affect the "exit" from violence/insurgency towards demobilization and reintegration. However, corruption may have redeeming values by serving the function of a power-sharing arrangement between antagonistic parties, thereby, reinforcing peace. Radical anti-corruption programs in post-conflicts situations may bring adverse results such as a renewal of violence. Aimed to fill the void in research on corruption in post-conflict situations, the article inquires about the links between corruption, peacebuilding and violent non-state actors. By combining various disciplinary approaches, the article theorizes the outcomes of corruption in post-conflict situations and discusses them in the context of Kosovo and Chechnya.